Microalbuminuria in Newly Diagnosed Type-2 Diabetes Mellitus: A study of Frequency and Risk Factors - Humaira Sami Ullah, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Microalbuminuria is associated with poor outcome in diabetes mellitus due to two main reasons. Firstly, microalbuminuria heralds progressive loss of renal function, i.e. diabetic nephropathy, which progresses to end stage renal disease, ultimately requiring dialysis. Secondly, microaalbuminuria in Type-2 Diabetes Mellitus (T2DM) also associated with increased mortality due to cardio-vascular (CV) risk. Aim: The aim of this study was to find out the frequency of microalbuminuria, and its associated risk factors, amongst patients with newly diagnosed type 2 diabetes mellitus. Material and method: This cross-sectional study was carried out at department of medicine, (Unit II), Bolan Medical Complex Hospital, Quetta from April 2021 to March 2022, after taking permission from the research committee. A total of 240 individuals of both genders and different age groups (ranged 15-75 years) with newly diagnosed type 2 diabetes mellitus were included. To adjust for possible impact modifiers, microalbuminuria (MA) was stratified by age, gender, BMI, habit of smoking, hypertension, education, occupation and place of residence. Following stratification, a p-value of less than 0.05 was deemed statistically significant, and the Chi-square test or Fisher's exact test, as appropriate, was used. For easy comprehension, the results were shown in tables. Results: A total of 240 individuals were included in this study. The overall frequency of microalbuminuria (MA) was 94(39.1%), in newly diagnosed type 2 diabetes mellitus patients. Microalbuminuria was found in 58(42.6%) males, which was more than that seen in females 38(36.5%), although the variance was not statistically noteworthy. When age groups were examined, the frequency of microalbuminuria increased with age. Microalbuminuria was substantially more common in individuals with hypertension 50(45.4%) with a statistically significant correlation (p-value = 0.04). MA was also more common in smokers than in non-smokers, with a difference that was somewhat significant (p = 0.05). It was somewhat more common in patients from rural regions than in those from urban areas (p = 0.47). Conclusion: The present study found that 39% of patients with newly diagnosed type 2 diabetes mellitus already had microalbuminuria at the time of diagnosis. This was more common in smokers and hypertensive individuals. Thus newly diagnosed type 2 diabetes mellitus patients, having a history of smoking and hypertension should have mandatory test for albuminuria during their first visit. This can not only prevent diabetic nephropathy’s progression, by early initiation of treatment, but also reduce morbidity and mortality secondary to cardiovscular disease. Key words: Microalbuminuria (MA), Newly diagnosed, Diabetes Mellitus type 2, T2DM, Nephropathy, Chronic kidney diseases (CKD).